Prison official perceptions of technology in prison - Mufarreh, Andrea (Punishment & society, 2022)
Several state prisons have provided tablets to imprisoned people which appears to be indicative of a larger trend to increase access to technology for imprisoned people. However, access to and the use of technology in prison has not been evaluated by social scientists. This study surveyed 70 prison officials from six states to report their attitudes toward access to and the use of tablets in prison for imprisoned people and for the prisons themselves. Survey results show that prison officials who work in prisons with more access to technology are more likely to believe technology to be a positive contribution for imprisoned people.